Nurses’ Intentions, Awareness and Barriers in Reporting Adverse Events: A Cross-Sectional Survey in Tertiary Hospitals in China - Zhao X; Shi C; Zhao L (Dove Medical Press, 2022)
Xiaoying Zhao,1 Chunhong Shi,2,3 Lihua Zhao1 1Handan First Hospital, Handan, 056000, People's Republic of China; 2School of Nursing, Xiangnan University, Chenzhou, People's Republic of China; 3Affiliated Hospital of Xiangnan University, Chenzhou, 423000, People's Republic of ChinaCorrespondence: Chunhong Shi, School of Nursing, Xiangnan University, 889 Chenzhou Avenue, Suxian District, Chenzhou, 423000, People's Republic of China, Tel +86 15907354840, Fax +86-735-2325007, Email shichunhong@xnu.edu.cnPurpose: This study explored nurses' intentions, awareness and barriers in reporting adverse events in tertiary hospitals in China. We also analyzed its associated factors to increase the chance to evaluate preventable errors, enhance care delivery, and improve patient outcomes.Patients and Methods: A cluster sampling method was used to recruit 1382 nurses from two tertiary hospitals in Chenzhou and Handan City. An online structured questionnaire was used to collect data, which included general information questionnaire (eight questions), reporting awareness questionnaire (eight items with scores ranging from 0 to 8), reporting intention questionnaire (15 items with scores ranging from 0 to 15), and reporting barriers questionnaire (22 items with scores ranging from 22 to 110).Results: We received 1565 completed questionnaires from 1734 potential participants (a response rate of 90.25%), with 1382 valid questionnaires, yielding an effective rate of 88.31%. The scores of reporting awareness, reporting intention, and reporting barriers in adverse events for nurses in tertiary hospitals were 8 (1), 15 (0), and 83.04 (± 12.21) out of 110, respectively. Reporting awareness and barriers to adverse events were positively correlated with nurses' intention to report adverse events (rs = 0.237 and 0.361, respectively; P < 0.001). Regression analyses showed that reporting awareness and barriers in adverse events and professional title influenced nurses' intention to report adverse events (P < 0.05) in tertiary hospitals.Conclusion: Nurses in tertiary hospitals have a strong intention to report adverse events. The higher the reporting awareness of adverse events or the fewer perceived reporting barriers, the stronger the nurses' intention to report. Hospital managers should deliver patient safety education and training for nurses, to increase their reporting awareness and decrease their perceived reporting barriers, improve their intention to report adverse events.Keywords: nurse, adverse events, patient safety, safety culture